2021
DOI: 10.1177/17411432211061445
|View full text |Cite
|
Sign up to set email alerts
|

How school leadership practices relate to student outcomes: Insights from a three-level meta-analysis

Abstract: The present study aims to generate broad insights from the large corpus of literature on the associations between a comprehensive range of school leadership practices and student outcomes in different school contexts. Three-level meta-analysis of 493 independent effects from 108 studies published since 2000 showed that the mean effect size was small at r  = 0.14. Effect sizes for leadership practices ranged from r’s  = 0.10 to .26. Results underscored the importance of different types of leadership practices r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…The results of school leadership studies are diverse but generally show that effective leadership engagement can have a positive impact on teacher job satisfaction, teacher collaboration, student outcomes, and overall positive school climate (e.g., Leithwood and Jantzi, 2008;Hallinger and Heck, 2010;Boberg and Bourgeois, 2016;Leithwood and Sun, 2018;Mora-Ruano et al, 2021;Tan et al, 2021). An effective leader can influence the attitudes and behaviour of teachers, thereby influencing their involvement in the work, which is critical to improving the success of organisations and ensuring educational quality (Hermanto and Srimulyani, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of school leadership studies are diverse but generally show that effective leadership engagement can have a positive impact on teacher job satisfaction, teacher collaboration, student outcomes, and overall positive school climate (e.g., Leithwood and Jantzi, 2008;Hallinger and Heck, 2010;Boberg and Bourgeois, 2016;Leithwood and Sun, 2018;Mora-Ruano et al, 2021;Tan et al, 2021). An effective leader can influence the attitudes and behaviour of teachers, thereby influencing their involvement in the work, which is critical to improving the success of organisations and ensuring educational quality (Hermanto and Srimulyani, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Another relevant piece of evidence is the linkage between school leadership and student academic achievement improvement. A metaanalysis research by Tan et al (2021) found that effective school leadership practises, such as setting clear goals and expectations, providing feedback, and creating a positive school climate have a significant positive effect on student achievement.…”
Section: Introductionmentioning
confidence: 99%
“…They can implement structures and time slots for meaningful teacher-principal collaboration and involve teachers in decisions on school improvement (Author et al 2022a;Author et al 2022b). The diverse ways in which principals interact with teachers affect both teachers' instructional quality and students' achievement (Grissom et al 2021;Tan et al 2021;Wu and Shen 2022). As Grissom et al (2021) summarise in their meta-analysis of 219 international studies, 'replacing a below-average elementary school principal with an above-average principal would result in an additional 2.9 months of math learning and 2.7 months of reading learning each year for students in that school.'…”
Section: The Relevance Of Principals' Leadership Practices and Profes...mentioning
confidence: 99%
“…In the ever-evolving landscape of education, the role of school leadership has become preeminent, as the challenges facing educational institutions continue to mount (Ghamrawi, 2010(Ghamrawi, , 2011(Ghamrawi, , 2013aLeroy et al, 2022;Tan et al, 2024). School leaders find themselves at the forefront of a complex and dynamic environment, where the demands and expectations placed upon them have reached unprecedented heights (Ghamrawi & Tamim, 2022;Chatzipanagiotou & Katsarou, 2023;Tamadoni et al, 2024).…”
Section: Introductionmentioning
confidence: 99%